2014
DOI: 10.1111/petr.12286
|View full text |Cite
|
Sign up to set email alerts
|

Child and family adjustment following pediatric solid organ transplantation: Factors to consider during the early years post‐transplant

Abstract: Adjusting to life after transplant can be challenging to pediatric solid organ transplant recipients and their families. In this review, we discuss a number of important factors to consider during the first 2-3 yr after transplant (defined as the "early years"), including transitioning from hospital to home, returning to physical activity, feeding and nutrition, school reentry, potential cognitive effects of transplant, family functioning, and QOL. We highlight steps that providers can take to optimize child a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…The pediatric heart recipients seemed to be unable to give a psychological meaning to the transplantation experience. The disease appeared thus to be a destabilizing factor impeding the reconstruction of the patient's sense of identity 23‐29 …”
Section: Discussionmentioning
confidence: 99%
“…The pediatric heart recipients seemed to be unable to give a psychological meaning to the transplantation experience. The disease appeared thus to be a destabilizing factor impeding the reconstruction of the patient's sense of identity 23‐29 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that parents have described the challenge to adjust to a "new normal" after heart transplant. 27,28 In addition, social and school functioning and behavioral issues are the most common domains where parents and children have identified challenges after transplantation. [12][13][14] Some studies have reported good HRQL post-heart transplant, with scores similar to the normative population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, caregivers of adult transplant recipients reported a desire for life before the chronic illness as a sense of security (Beckmann et al., ) and parents of heart transplant recipients have described the importance of normality (Green, Meaux, Huett, & Anley, ). Paying attention to child and family adjustment after SOT continues after the 6‐month time period included in this study, as it has been reported to be an important concern 2–3 years after transplant (Brosig et al., ). Nurses can help prepare parents to face the future by helping them anticipate that it is normal to expect vigilance and need for management of finances in long term.…”
Section: Discussionmentioning
confidence: 99%